2013
DOI: 10.1007/978-3-642-41822-8_49
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimisation of JPEG2000 Part 2 Wavelet Packet Structures for Polar Iris Image Compression

Abstract: Abstract. The impact of using evolutionary optimised wavelet subband stuctures as allowed in JPEG2000 Part 2 in polar iris image compression is investigated. The recognition performance of two different feature extraction schemes applied to correspondingly compressed images is compared to the usage of the dyadic decomposition structure of JPEG2000 Part 1 in the compression stage. Recognition performance is significantly improved, provided that the image set used in evolutionary optimisation and actual applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…JPEG Q-table optimisation has already been considered in face recognition [15] which leads to superior recognition performance as compared to the standard matrix. A further example is the optimisation of JPEG 2000 Part 2 wavelet packet decomposition structures with respect to optimising iris recognition accuracy which provides better results compared to ratedistortion optimised wavelet packet structures [9]. These observations raise the question if compression algorithms exhibiting better rate-distortion performance are also better in a biometric recognition context.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…JPEG Q-table optimisation has already been considered in face recognition [15] which leads to superior recognition performance as compared to the standard matrix. A further example is the optimisation of JPEG 2000 Part 2 wavelet packet decomposition structures with respect to optimising iris recognition accuracy which provides better results compared to ratedistortion optimised wavelet packet structures [9]. These observations raise the question if compression algorithms exhibiting better rate-distortion performance are also better in a biometric recognition context.…”
Section: Related Workmentioning
confidence: 97%
“…JPEG-XR is found to be competitive to the current standard JPEG 2000 while exhibiting significantly lower computational demands. For JPEG 2000, Hämmerle et al show that JPEG 2000 Part 2 can improve recognition accuracy by employing adapted wavelet packet basis instead of the fixed dyadic Part 1 decomposition [9] and also, JPEG 2000 region-of-interest coding is shown to by beneficial by assigning a higher bitrate to iristexture regions in the image [10].…”
Section: Related Workmentioning
confidence: 97%
“…Aforementioned studies as well as standardisation activities analyse the effects of different image compression standards on biometric recognition systems in order to elaborate a common standard for the compression of biometric data which still enables reliable authentication [19]. Further, diverse compression techniques have been explicitly designed for distinct biometric modalities, for example, in [20,[35][36][37][38]. Hence, in various application scenarios lossless or slight compression is considered in bi-lateral compression scenarios, that is, probe and reference images…”
Section: Introductionmentioning
confidence: 99%
“…Recent work [10] showed that for polar iris image (IREX K16) common subband structure selection strategies including rate-distortion optimising ones are not very successful as compared to the dyadic decomposition scheme (defined in the Part 1 of the JPEG2000 standard suite). However, we were able to demonstrate some limited performance gain using evolutionary optimization for selecting wavelet packet subband structures [11]. In this work, we re-investigate the usage of common wavelet packet subband structure selection strategies including rate-distortion optimising ones for rectilinear K1/K3 imagery.…”
Section: Introductionmentioning
confidence: 99%